1993
DOI: 10.1002/hep.1840180404
|View full text |Cite
|
Sign up to set email alerts
|

High carrier rate after hepatitis B virus infection in the elderly

Abstract: An outbreak of hepatitis B virus infection occurred in a nursing facility; it involved 31 patients with sequelae of cerebral vascular accidents (15 men and 16 women; mean age, 77.4 +/- 9.3 yr). HBsAg disappeared within 6 mo in 9 patients and persisted during an observation period of more than 6 mo in 13; the remaining 9 patients were lost to follow-up while they carried HBsAg. Thus 13 of 22 patients followed (59%) became HBsAg carriers. We amplified a part of the S gene (436 nucleotides) with polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…An outbreak of HBV infection from an HBV-positive health care worker with dermatitis in his hand occurred in 31 elderly persons living at a long-term nursing facility in Japan over a period of about 30 months [Kondo et al, 1993]. Of note, after the initiation of use of disposable gloves by the health care worker, however, no new cases of HBV infection occurred at that facility, indicating the occurrence of HBV transmission from a health care worker to patients via injured skin.…”
Section: Discussionmentioning
confidence: 97%
“…An outbreak of HBV infection from an HBV-positive health care worker with dermatitis in his hand occurred in 31 elderly persons living at a long-term nursing facility in Japan over a period of about 30 months [Kondo et al, 1993]. Of note, after the initiation of use of disposable gloves by the health care worker, however, no new cases of HBV infection occurred at that facility, indicating the occurrence of HBV transmission from a health care worker to patients via injured skin.…”
Section: Discussionmentioning
confidence: 97%
“…It is 2.6% in person between 17 to 55 years, while after 55 years it was 0.213%. In screening of elderly persons living in tents of Kumbh Mela also showed low positivity of HBsAg (1.19%).Hepatitis B infection is rare in most of the European countries in elderly persons [17] but a French study done in person over 65 years of age admitted in rehabilitation ward and nursing home revealed a very high carrier rate (16.7%) against 5% of adult population [17] Another study have done in old peoples and found a very high incidence of hepatitis B carrier (59%) [18] Probably in our country mostly elderly person becomes religious have less sexual activity and because of this incidence of hepatitis B carrier is less. Liver Function Test (LFT) done in 19 cases showed mild abnormalities in all cases but none of the person had elevated total bilirubin or direct bilirubin.…”
Section: Discussionmentioning
confidence: 98%
“…(B) Phylogenetic tree of the S gene sequences (681bp) of the study cases and 91 S gene sequences (681bp) retrieved from the DDBJ/EMBL/GenBank. only a few become carriers, however, the carrier rate after HBV infection is high among the elderly [Kondo et al, 1993], because of impairment of the cellular and humoral immune responses in the elderly. These reasons may be related to the high risk and facilitate spread of HBV among the residents of nursing homes for the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In the study that used genetic analysis to determine the transmission route of HBV infection in a nursing home for the aged, only point mutations in a part of the S gene sequence were compared [Kondo et al, 1993]. Analysis of the antigenic subtype of HBV or DNA sequence comparisons may provide supporting evidence for putative transmission [Zuckerman et al, 1995], but it is often difficult to discriminate between various HBV strains in countries like Japan where the one subtype of HBV is predominant [Shiina et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation